How to build a cluster: the formation and evolution of galaxies in high-redshift clusters and protoclusters - Cooke, Elizabeth A. (2016)
High redshift galaxy protoclusters are the precursors of today’s massive clusters; the sites of formation of the most massive galaxies in the present-day Universe. By studying these immature structures we can directly analyse the formation of galaxies in the densest environments without relying on extrapolations from low redshift. Finding protoclusters is challenging due to the need for very wide and deep surveys. Radio-loud active galactic nuclei (RLAGN) have been shown to preferentially reside in overdense environments at z > 1. By using these bright radio sources as beacons, protoclusters may be efficiently selected, without the need for large, blind surveys. In this thesis I study the properties of galaxies in high redshift (z > 1.3) clusters and protoclusters selected around RLAGN.